PENINGKATAN KUALITAS PEMBELAJARAN MELALUI MODEL TWO STAY TWO STRAY DENGAN MEDIA POWERPOINT - Edi Warman Purba (JURNAL GLOBAL EDUKASI, 2018)
Abstract: Social studies subjects are arranged in a systematic, comprehensive, and integrated manner in the learning process towards maturity and success in life in society. This research was motivated by the results of self-reflection of researchers in social studies learning in the fifth grade of 013822 Simpang Empat Asahan Elementary School 2018/2019 Academic Year, which showed an increase. Some of the problems that cause these conditions include: (1) teacher skills: the teacher has not maximally used the learning model; (2) student activities: in the group work activities only a few students are active, and other students play alone; (3) learning outcomes: only 13 of the 24 students who received learning outcomes reached KKM. The results of the study showed that the skills of the teachers in the first cycle obtained a good category, in the second cycle and in the third cycle the categories were very good. The average activity of students in the first cycle obtained enough categories, in the second cycle it got a good category, and in the third cycle it got a very good category. The learning outcomes of the students' knowledge in the first cycle get enough categories, in the second cycle and in the third cycle they get a good category. Keywords: Learning Quality, Two Stay Two Stray Abstrak: Mata pelajaran IPS disusun secara sistematis, komprehensif, dan terpadu dalam proses pembelajaran menuju kedewasaan dan keberhasilan dalam kehidupan di masyarakat. Penelitian ini dilatar belakangi oleh hasil refleksi diri peneliti dalam pembelajaran IPS pada kelas V SD Negeri 013822 Simpang Empat Kabupaten Asahan Tahun Pelajaran 2018/2019, yang menunjukkan perlu adanya peningkatan. Beberapa permasalahan penyebab kondisi tersebut diantaranya: (1) keterampilan guru: guru belum maksimal menggunakan model pembelajaran ; (2) aktivitas siswa: dalam kegiatan keja kelompok hanya beberapa siswa saja yang aktif, dan siswa yang lain bermain sendiri; (3) hasil belajar: hanya 13 dari 24 siswa yang mendapat hasil belajar mencapai KKM.Hasil penelitian menunjukkan bahwa keterampilan guru pada siklus I memperoleh kategori baik, pada siklus II dan pada siklus III memperoleh kategori sangat baik. Rata-rata aktivitas siswa pada siklus I memperoleh kategori cukup, pada siklus II memperoleh kategori baik, dan pada siklus III memperoleh kategori sangat baik. Hasil belajar ranah pengetahuan siswa pada siklus I memperoleh kategori cukup, pada siklus II dan pada siklus III memperoleh kategori baik. Kata kunci: Kualitas Pembelajaran, Two Stay Two Stray